Marine motifs embroidered on the Surka - Mumbai Archive Project Team (Jio Institute, 2024)
The front part of the surka is embroidered with maritime motifs such as fish, crabs, and boats. The surka is a long piece of cloth wrapped around the waist and legs, tied in a way that gives a triangular shape at the front. Traditionally, Koli fishermen wore a short dhoti known as langoti for sea fishing, reserving the surka for festivals and special occasions.